Electrode active material, its preparation method, electrode piece and battery

By using carbon coating-treated metal oxidized particles as battery active materials, the problems of low battery energy density and charging efficiency in the prior art are solved, and a higher charging capacity and a lighter material structure are achieved.

JP7669527B2Active Publication Date: 2025-04-28CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023565976
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-04-18
Publication Date
2025-04-28
Estimated Expiration
2042-04-18

AI Technical Summary

Technical Problem

Existing battery active materials are difficult to meet the needs of high energy density and fast charging, and traditional carbon coating treatment methods cannot effectively improve battery performance.

Method used

Battery active materials containing carbon-coated metal oxidized particles, where metal oxidized particles comply with specific chemical formulas, and optimize conductivity and stability by controlling carbon content and particle size.

Benefits of technology

The charging capacity per gram of the battery is increased, the weight of material after discharge is reduced, the total weight of battery parts is reduced, and the energy density and charging efficiency of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669527000006
    Figure 0007669527000006
  • Figure 0007669527000007
    Figure 0007669527000007
  • Figure 0007669527000008
    Figure 0007669527000008
Patent Text Reader

Abstract

The present application provides an electrode active material, a preparation method thereof, an electrode piece and a battery, the electrode active material comprising carbon-coated metal oxide particles, the metal oxide particles satisfying the following formula (2), and A c M d O e (2), in formula (2), the A element is selected from one or more alkali metal elements or alkaline earth metal elements, the M element is selected from one or more transition metal elements having a relative atomic mass less than 65, and c>0, d>0, and e>0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of lithium batteries, in particular to electrode active materials, their preparation methods, pole pieces and batteries. [Background technology]

[0002] Energy conservation and emission reduction are the keys to the sustainable development of the automobile industry, and electric vehicles have become an important component of the sustainable development of the automobile industry due to their energy conservation and environmental protection advantages. Battery technology is also an important factor related to the development of electric vehicles. With the rapid development of today's society, the scope of use of existing energy is becoming wider and wider, but the harmful gases generated by fossil fuels have caused significant side effects on the environment, and at the same time, the shortage of fossil energy makes it impossible to meet people's currently increasing energy demand. Therefore, finding new clean energy to replace fossil energy is one of the most effective ways to solve this problem. Batteries have stable performance, high specific energy, and can be recycled and used many times, which has attracted great interest, and electrode active materials are an important component of batteries and are the key to determining the quality of batteries.

[0003] As the market, especially the power battery market, has higher and higher requirements for battery energy density and charging efficiency, the requirements for electrode active materials are also higher. Conventional electrode active materials have not been able to meet the requirements for energy density and specific capacity of next-generation batteries. In addition, in order to improve the performance of batteries, the electrode active materials are often subjected to post-treatment of carbon coating to optimize the transmission of electrons through the electrode active materials. However, conventional treatment methods have not been able to reliably improve battery performance. Summary of the Invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art, and therefore aims to provide an electrode active material that has a high charge capacity per gram and is advantageous for improving battery capacity.

[0005] A first aspect of the present application provides an electrode active material comprising carbon-coated metal oxide particles, the metal oxide particles satisfying the following formula (2): A c M d O e (2) In formula (2), the A element is selected from one or more alkali metal elements or alkaline earth metal elements, the M element is selected from one or more transition metal elements having a relative atomic mass less than 65, and c>0, d>0, and e>0.

[0006] In the electrode active material provided by the present application, the atomic mass of the transition metal element is relatively small, and the carbon-coated metal oxide particles, when containing the same number of A ions, have a higher charge capacity per gram, the material remaining after discharge is lighter, and the weight of the total electrode piece is smaller, which can improve the proportion of the electrode active material in the battery and the energy density.

[0007] In any embodiment, the A element is selected from one or more of Li, Na, K, Mg, and Ca. The above-mentioned metal oxides have high charge capacity per gram and high energy density, and the raw materials are abundant and easy to obtain, suitable for various batteries, and have good application prospects.

[0008] In any embodiment, the metal oxide is Li 2 M 1 O 2 , Li 2 M 2 O 3 , Li 3 M 3 O 4 , Li 5 M 4 O 4 , Li 6 M 5 O 4 wherein M 1 is selected from one or more of Ni, Co, Fe, Mn, and Cu, and M 2is selected from one or more of Mn, Sn, Mo, Ru, and Ir, and M 3 is selected from one or more of V, Nb, Cr, and Mo; M 4 is selected from one or more of Fe, Cr, V, and Mo, and M 5 is selected from one or more of Co, V, Cr, and Mo. The above metal oxides have high charge capacity per gram, high energy density, and good application prospects.

[0009] In any embodiment, the metal oxide is Li 2 NiO 2 , Li 2 CuO 2 , Li 2 MnO 3 , Li 3 VO 4 , Li 5 FeO 4 , Li 6 Chief of Staff 4 The preparation method of the above-mentioned lithium-rich metal oxide is mature, has high charge capacity per gram and high energy density, can meet the demand for rechargeable lithium batteries used in next-generation large-scale power grid storage and electric vehicles, and has high application prospects.

[0010] In any embodiment, the molar ratio of A element to M element is c:d≧2, calculated based on the total moles of the elements in the electrode active material. In the metal oxide, the more the number of A atoms is relative to M atoms, the higher the charge capacity per gram of the electrode active material will be.

[0011] In any embodiment, the carbon content of the electrode active material is 2wt%-20wt%, and optionally 5wt%-15wt%, based on the total weight of the electrode active material. With the appropriate carbon coating content, the electrode active material has low powder resistivity, high material stability and electronic conductivity, and excellent carbon coating effect, which is advantageous for improving battery capacity.

[0012] In any embodiment, the electrode active material comprises a doping element, and the ratio of the solubility product constant of the hydroxide of the doping element to each of the hydroxides of the M element is 10 -5 ~10 5 The doping element can be selected from one or more of Mg, Zn, Al, and Ti. The electrode active material contains a doping element, which can further improve the stability of the electrode active material and extend the service life of the battery. The ratio of the solubility product constant of the hydroxide of the doping element to that of the hydroxide of the M element is 10 -5 ~10 5 Therefore, the difference in solubility product between the hydroxide of the doping element and the hydroxide of the M element is too large, which can result in uneven doping and even the precipitation of the doping element alone. This maximizes the utility of the doping element and contributes to improving the charge capacity and energy density per gram of the electrode active material.

[0013] In any embodiment, the powder resistivity of the carbon-coated metal oxide particles is less than 1000 Ω·cm, optionally less than 350 Ω·cm, more optionally less than 10 Ω·cm, and even more optionally less than 5 Ω·cm. The carbon-coated metal oxide particles have low powder resistivity, high material stability and high electronic conductivity, and good carbon coating effect, which is favorable for improving battery capacity.

[0014] In any embodiment, the median particle diameter Dv50 of the carbon-coated metal oxide particles is within the range of 100 to 900 nm, and optionally within the range of 300 to 700 nm. The carbon-coated metal oxide particles have an appropriate median diameter, and the electrode active material has a short ion transmission path during charging, high kinetics, and high charge capacity per gram, while also having an appropriate specific surface area, and is unlikely to cause a decrease in charge capacity per gram due to aggregation.

[0015] A second aspect of the present application provides a method for preparing an electrode active material, the method comprising providing carbon-composite oxide particles, the oxide satisfying the following formula (1): M a O b (1) In formula (1), M element is selected from one or more transition metal elements having a relative atomic mass of less than 65, a>0, b>0; The carbon-composite metal oxide particles and the A source are sintered to obtain carbon-coated metal oxide particles, and the metal oxide satisfies the following formula (2): A c M d O e (2) In formula (2), the A element is selected from one or more of alkali metal elements or alkaline earth metal elements, the M element is selected from one or more of transition metal elements having a relative atomic mass less than 65, and c>0, d>0, and e>0.

[0016] In any embodiment, the carbon-coated metal oxide particles prepared by the above method have high integrity of the outer carbon layer coating and low powder resistivity of the material. In addition, the surface carbon layer in the carbon composite oxide particles is effectively utilized to suppress the growth and aggregation of metal oxide particles during the sintering process, and the size of the carbon-coated metal oxide particles is limited to the submicron to nano order, so that the ion transmission path during the charging process of the carbon-coated metal oxide particles is short, the kinetics is high, and the charging capacity per gram is higher. At the same time, the post-treatment of the carbon coating on the carbon-coated metal oxide particles can be avoided, which effectively improves the stability of the carbon-coated metal oxide particles and reduces the manufacturing cost.

[0017] In any embodiment, the powder resistivity of the carbon composite oxide particles is less than 100 Ω·cm, and optionally less than 10 Ω·cm. The carbon composite oxide particles have low powder resistivity, and the carbon element has high composite uniformity and good dispersibility, so that the electrode active material prepared using the carbon composite oxide particles as a precursor does not require post-treatment of carbon coating, which solves the adverse effects of the normal post-treatment of carbon coating, improves the stability of the electrode active material, and reduces the manufacturing cost. At the same time, the carbon composite oxide particles have low powder resistivity and good carbon dispersibility, so that the carbon-coated metal oxide particles prepared using the carbon composite oxide particles as a precursor have high coating integrity of the carbon layer, and the powder resistivity of the carbon-coated metal oxide particles is low, thereby improving the battery capacity.

[0018] In any embodiment, the median particle size Dv50 of the carbon composite oxide particles is within a range of 10 to 200 nm, and optionally within a range of 20 to 100 nm. Controlling the median particle size of the carbon composite oxide particles within an appropriate range is advantageous for controlling the particle size of the carbon-coated metal oxide, reducing the powder resistivity of the carbon-coated metal oxide, and improving the charge capacity per gram.

[0019] In any embodiment, the carbon content in the carbon composite oxide particles is 10wt%-40wt%, and optionally 20wt%-30wt%, based on the total weight of the carbon composite oxide particles. Controlling the carbon content in the carbon composite oxide particles within an appropriate range is advantageous for reducing the powder resistivity of the electrode active material and improving its charge capacity per gram.

[0020] In any embodiment, the sintering temperature is in the range of 500-700° C., optionally in the range of 550-650° C., and / or the sintering time is in the range of 4-20 h, optionally in the range of 8-12 h. Controlling the sintering temperature and / or time within an appropriate range is advantageous for preparing carbon-coated metal oxide particles with low powder resistivity, appropriate median particle size Dv50, and high charge capacity per gram.

[0021] In any embodiment, the A source is selected from one or more of an oxide, salt, or hydroxide of an alkali metal or alkaline earth metal. The method is versatile and can synthesize multiple types of carbon-coated metal oxide particles as needed.

[0022] In any embodiment, the A source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, and lithium acetate, and the molar ratio of the lithium element in the A source to the M element in the carbon composited oxide particles is in the range of 5.5 to 1. The lithium-rich metal oxides prepared by this method exhibit low powder resistivity and high charge capacity per gram.

[0023] In an optional embodiment, the carbon composite oxide particles are prepared by liquid phase precipitation, which is simple, low cost, and widely applicable.

[0024] A third aspect of the present application provides a pole piece comprising a current collector and an electrode active material layer provided on at least one surface of the current collector and comprising the electrode active material of the first aspect, the pole piece enabling a battery to have a high capacity.

[0025] A fourth aspect of the present application provides a battery comprising the electrode active material of the first aspect or the pole piece of the third aspect, the battery having a high capacity.

[0026] The above description is only an overview of the technical solution of the present application, which can be implemented in accordance with the contents of the specification, in order to make the technical means of the present application more clearly understandable. In order to facilitate a clearer understanding of the above and other objectives, features and advantages of the present application, the following provides specific embodiments of the present application. [Brief description of the drawings]

[0027] In the accompanying drawings, the same reference numerals in several accompanying drawings indicate the same or similar parts or elements, unless otherwise specified. The accompanying drawings are not necessarily to be drawn to scale. It should be understood that the accompanying drawings depict only some embodiments disclosed herein and should not be considered as limiting the scope of the present application.

[0028] [Figure 1] 1 is a scanning electron microscope (SEM) photograph of Fe2O3@C provided in Example 3.

[0029] [Diagram 2] FIG. 1 is a transmission electron microscope (TEM) image of Fe2O3@C provided in Example 3.

[0030] [Diagram 3] 1 is an X-ray diffraction (XRD) diagram of Fe2O3@C provided in Example 3.

[0031] [Figure 4] FIG. 2 is a transmission electron microscope (TEM) image of LiFeO@C provided in Example 25.

[0032] [Diagram 5] FIG. 2 is an X-ray diffraction (XRD) diagram of Li5FeO4@C provided in Example 25.

[0033] [Figure 6] FIG. 26 is the first charge curve of Li5FeO4@C provided in Example 25. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Hereinafter, the embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly explain the technical solution of the present application, and are used as examples only, and do not limit the scope of protection of the present application.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art of this application, and the terms used herein are merely for the purpose of describing specific examples and are not intended to be limiting of this application, and the terms "including", "having", and any variations thereof in the specification, claims, and above description of the drawings are intended to have a non-exclusive covering implication.

[0036] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are merely for distinguishing different objects, and cannot be understood as indicating or implying a relative importance, or implying a number, a particular order, or a primary-subordinate relationship of the indicated technical features. In the description of the embodiments of the present application, "plurality" means two or more, unless otherwise specifically limited.

[0037] Reference to an "embodiment" herein means that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the present application. The phrases appearing in each location in the specification do not necessarily refer to the same embodiment, nor do they refer to embodiments that are mutually exclusive, independent, or alternative to other embodiments. Those skilled in the art will explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.

[0038] In the description of the embodiments of the present application, the term "and / or" is simply a relational relationship describing related objects, and can indicate, for example, that there can be three relations, A and / or B, where A exists alone, A and B exist simultaneously, and B exists alone. Note that in this specification, the character " / " generally indicates that the related objects before and after it are in an "or" relationship.

[0039] In describing the embodiments of the present application, the term "multiple" means two or more (including two); similarly, "multiple sets" means two or more sets (including two sets); and "multiple sheets" means two or more sheets (including two sheets).

[0040] In describing the embodiments of the present application, the orientations or positional relationships indicated by technical terms such as "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial direction," "radial direction," "circumferential direction," and the like are orientations or positional relationships based on the accompanying drawings, and are intended merely to facilitate and simplify the description of the embodiments of the present application, and do not indicate or imply that the indicated devices or elements have a specific orientation so as to be configured and operated in a specific orientation, and therefore cannot be understood as limitations of the embodiments of the present application.

[0041] In the description of the embodiments of the present application, unless otherwise expressly specified and limited, the technical terms "attached", "interconnected", "connected", "fixed", etc. should be understood in a broad sense, and may mean, for example, a fixed connection, a removable connection, an integral connection, a mechanical connection, an electrical connection, a direct connection, an indirect connection via an intermediate medium, an internal communication between two elements, or an interactive relationship between two elements. The specific meanings of the above terms in the embodiments of the present application can be understood by those skilled in the art according to the specific circumstances.

[0042] In the prior art, the electrode active material is mixed with the carbon material and then carbon-coated to improve the capacity of the battery, and in particular, the lithium-rich metal oxide is carbon-coated to solve the problem of poor stability and dynamics of the lithium-rich metal oxide. However, the applicant has found in his research that the carbon-coated post-treatment has the following shortcomings: First, the carbon-coated post-treatment has poor coating integrity and strong randomness; Second, during the carbon-coated post-treatment of the lithium-rich metal oxide, the surface is prone to undergo phase transition, and the active lithium inside the material is released to generate lithium carbonate as a by-product on the surface, which reduces the charging capacity per gram of the lithium-rich metal oxide; More importantly, during the carbon-coated post-treatment of the lithium-rich metal oxide, the agglomeration of the lithium-rich metal oxide is increased, and the particle size of the particles is further increased, which worsens the delithiation dynamics and reduces the charging capacity per gram.

[0043] Based on this, in an embodiment according to the first aspect of the present application, a precursor of an electrode active material is provided that includes carbon-composite oxide particles, the oxide satisfying the following formula (1): M a O b (1) In formula (1), M element is selected from one or more transition metal elements having a relative atomic mass of less than 65, and can be selected from one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Mn, Sn, Mo, Ru, Ir, V, Nb, and Cr, a>0, b>0, and the powder resistivity of the carbon-composite oxide particles is less than 100 Ω cm.

[0044] The precursor of the electrode active material refers to a material that can be a raw material for preparing the electrode active material. In some embodiments, the upper limit of the powder resistivity of the carbon composite oxide particles can be selected from 50 Ω cm, 40 Ω cm, 30 Ω cm, and 20 Ω cm.

[0045] In this specification, the term "powder resistivity" is a parameter for expressing the electrical conductivity of the material itself, which is different from the resistivity of the pole piece. Generally, the powder resistivity is measured by using a tester such as a four-probe according to GB / T30835-2014 "Carbon composite lithium iron phosphate positive electrode material for lithium ion batteries".

[0046] In some embodiments, the carbon composite oxide particles are composite materials containing carbon and oxide particles. It is understood that the carbon and oxide particles can be composited by any method, such as physical mixing, chemical composite, etc. Specifically, the carbon and oxide particles can be composited by agitation, grinding, ultrasonic, in-situ growth, grafting, coating, etc.

[0047] In some embodiments, M a O b is M 1 O.M. 2 O 2 , M 3 2 O 5 , M 4 2 O 3 , M 5 O. 1 contains one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, and Cu, and M 2 contains one or more of Mn, Sn, Mo, Ru, and Ir, 3 contains one or more of V, Nb, Cr, and Mo, and M 4 contains one or more of Fe, Cr, V, and Mo, and M 5 contains one or more of Co, V, Cr, and Mo.

[0048] The transition metal elements refer to a series of metal elements in the d and ds regions of the periodic table, where the d region elements include the elements in groups IIIB to VIIB and VIII of the periodic table, and the ds region includes the elements in groups IB to IIB of the periodic table.

[0049] The precursor of the electrode active material provided in the present application includes carbon composite oxide particles, in which the carbon element has high composite uniformity and good dispersibility, so that the carbon composite oxide particles have low powder resistivity, and the electrode active material prepared using this precursor does not require post-treatment of carbon coating, solving the adverse effects of the above-mentioned normal post-treatment of carbon coating, improving the stability of the electrode active material, and reducing the manufacturing cost. At the same time, the carbon composite oxide particles have low powder resistivity and good carbon dispersibility, so that the electrode active material prepared using this precursor has high coating integrity of the carbon layer, low powder resistivity of the electrode active material, and improves the battery capacity. Furthermore, the surface carbon layer in the carbon composite oxide particles is effectively used to suppress the growth and aggregation of the electrode active material, and the size of the electrode active material is limited to the submicron to nano order, so that the ion transmission path during the charging process of the electrode active material is short, the kinetics is high, the stability is high, and the charging capacity is higher. Moreover, since the atomic mass of the transition metal element in the carbon composite oxide particles is relatively small, the prepared electrode active material has a higher charge capacity per gram, is lighter in residual material after discharge, and accounts for a smaller weight in the total electrode piece, which can further increase the proportion of electrode active material in the battery and the energy density.

[0050] In some embodiments, the powder resistivity of the carbon composite oxide particles is less than 10 Ω cm, optionally less than 1 Ω cm, and the upper powder resistivity limit can be selected from 9 Ω cm, 8 Ω cm, 7 Ω cm, 6 Ω cm, 5 Ω cm, 4.25 Ω cm, 3.58 Ω cm, 2.78 Ω cm, 2.28 Ω cm, 2.15 Ω cm, 1.38 Ω cm, 1.02 Ω cm, 0.98 Ω cm, 0.95 Ω cm, 0.56 Ω cm, 0.42 Ω cm, 0.31 Ω cm, 0.3 Ω cm, 0.28 Ω cm, 0.26 Ω cm, 0.25 Ω cm, 0.24 Ω cm, 0.23 Ω cm, 0.22 Ω cm, 0.21 Ω cm, and 0.19 Ω cm. By reducing the powder resistivity of the carbon composite oxide particles, the resistivity of the prepared electrode active material can be reduced, and the charge capacity per gram of the electrode active material can be improved.

[0051] In some embodiments, the mass content of carbon element in the carbon composite oxide particles is 10-40%, and optionally 20-30%. In some embodiments, the mass content of carbon element in the carbon composite oxide particles can be selected from 10%, 18%, 20%, 22%, 23%, 24%, 25%, 30%, and 40%.

[0052] In some embodiments, a carbon content analyzer is used to measure the mass content of carbon element in the carbon-composite oxide particles. In this specification, the mass content of carbon element in the carbon-composite oxide particles can be adjusted by changing the mass of the added carbon source during the preparation of the carbon-composite oxide.

[0053] If the mass content of carbon element in the carbon composite oxide particles is too high, the ratio of oxide in the carbon composite oxide particles decreases, the carbon material itself aggregates, and the composite effect is likely to deteriorate. By controlling the mass content of carbon element in the carbon composite oxide particles within an appropriate range and uniformly compositing carbon, carbon composite oxide particles having a uniform particle size distribution and high dispersibility of carbon element can be obtained, and further the powder resistivity of the carbon composite oxide particles and the electrode active material prepared using the carbon composite oxide particles as a precursor can be reduced, thereby improving the battery capacity.

[0054] In some embodiments, the carbon composite oxide particles have a median particle size Dv50 of 10 to 200 nm, optionally 20 to 100 nm. In some embodiments, the carbon composite oxide particles have a median particle size Dv50 selected from 20 nm, 30 nm, 40 nm, 45 nm, 47 nm, 58 nm, 60 nm, 61 nm, 62 nm, 65 nm, 68 nm, 70 nm, 75 nm, 80 nm, 83 nm, 94 nm, 100 nm, 110 nm, and 200 nm.

[0055] In this specification, the median particle size Dv50 of the carbon composite oxide particles has a meaning well known in the art. The median particle size Dv50 is also called the average particle size, and represents the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%. It can be measured using methods and measuring instruments known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method.

[0056] If the particle size of the carbon composite oxide particles is too small, the specific surface area is likely to be too large and the specific surface energy is likely to be too high, so that in the process of preparing the electrode active material, the carbon composite oxide particles themselves aggregate and reduce dispersibility. If the particle size of the carbon composite oxide particles is too large, the composite effect of carbon and oxide particles is likely to decrease. If the median particle size Dv50 of the carbon composite oxide particles is controlled within an appropriate range, it is advantageous for controlling the particle size of the electrode active material prepared using the carbon composite oxide particles as a precursor, and is advantageous for preparing an electrode active material with low powder resistivity, appropriate median particle size Dv50, and high charge capacity per gram.

[0057] In an embodiment according to the second aspect of the present application, there is provided a method for preparing a precursor of the electrode active material, the method comprising the steps of dispersing a carbon source in an aqueous solution containing M ions to obtain a mixed solution, adjusting and controlling the pH value of the mixed solution until it becomes alkaline to obtain an alkaline mixed solution, subjecting the alkaline mixed solution to a precipitation reaction to obtain a precipitate, separating and washing the precipitate to obtain a precursor, and dehydrating and drying the precursor to prepare and obtain a precursor of the electrode active material, the precursor of the electrode active material comprising carbon-composite oxide particles, the oxide satisfying the following formula (1): M a O b (1) In formula (1), M element is selected from one or more transition metal elements having a relative atomic mass of less than 65, and can be selected from one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Mn, Sn, Mo, Ru, Ir, V, Nb, and Cr, a>0, b>0, and the powder resistivity of the carbon-composite oxide particles is less than 100 Ω cm.

[0058] In some embodiments, the aqueous solution of M ions is prepared by dissolving a salt having M ions in water. In some embodiments, the concentration of M element in the mixture is 0.5-10 mol / L. In some embodiments, the carbon source in the mixture is dispersed by various dispersion methods, such as ultrasonic waves, stirring, etc. By dispersing the carbon source in an aqueous solution containing M ions, the M ions are uniformly adsorbed on the carbon source, which functions as a substrate in the subsequent precipitation reaction process, and the M ions are uniformly dispersed on the substrate as a nucleation reactant, thereby avoiding the growth of aggregates of the generated precipitates and suppressing the growth of oxide particles.

[0059] In some embodiments, the pH value of the mixed solution is adjusted and controlled by adjusting the flow rate and flow rate of adding the strong alkaline solution. The strong alkaline solution is selected from one or more of sodium hydroxide and potassium hydroxide. The hydroxyl group in the strong alkaline solution is rapidly ionized from the solution and used to control the growth process of the precipitate. Optionally, the concentration of the strong alkaline solution is 1-10 mol / L. In some embodiments, the strong alkaline solution is added to the mixed solution after stirring the mixed solution for a certain period of time. In some embodiments, the strong alkaline solution is added to the mixed solution after stirring the mixed solution for 0.1-2 h. In some embodiments, the strong alkaline solution is added to the mixed solution after stirring the mixed solution for 1 h. In some embodiments, the strong alkaline solution and the mixed solution are added in parallel to the reaction kettle, and the flow rate of the strong alkaline solution is 0.01-0.5 times the flow rate of the mixed solution. In some embodiments, the strong alkaline solution and the mixed solution are added in parallel to the reaction kettle, and the flow rate of the strong alkaline solution is 0.1 times the flow rate of the mixed solution. Before the addition of the strong alkaline solution, the mixture is stirred to increase the dispersion of the M ions and the carbon source, assisting the adsorption of the M ions on the carbon source, preventing the rapid growth of the carbon composite oxide particles, and contributing to the preparation of carbon composite oxide particles with a high degree of dispersion and a uniform particle size.

[0060] In some embodiments, the precipitation reaction is carried out under stirring conditions. In some embodiments, the stirring intensity is 100 to 500 revolutions per minute. In some embodiments, the precipitate is separated by extraction filtration or centrifugation after the reaction is completed. In some embodiments, to wash the precipitate, the precipitate is wet washed multiple times with distilled water or absolute ethanol. In some embodiments, the washed product is placed in an oven to dry, thereby obtaining carbon-composite oxide particles.

[0061] A precipitation reaction is a reaction in which the target product in a solution is precipitated as a solid phase. In this specification, M ions are precipitated in an alkaline mixture to obtain a precipitate.

[0062] This preparation method is simple and easy to carry out, suitable for preparing various carbon composite oxide particles, and has the characteristics of low cost and easy to be widely used. This method adds a carbon source during the reaction to act as a nucleation site for precipitates, inhibiting the aggregation of precipitates, and also enhances the composite effect of carbon and oxide, thereby reducing the resistivity of the carbon composite oxide particles, so that the carbon composite oxide particles prepared have the characteristics of uniform particle size distribution, high dispersibility, low powder resistivity, high carbon content, etc.

[0063] In some embodiments, the pH value of the alkaline mixture is in the range of 9 to 13, optionally in the range of 10 to 12. In some embodiments, the pH value of the alkaline mixture can be selected from any one of 8, 9, 10, 11, 11.6, 11.8, 12, and 13.

[0064] The pH value of the alkaline mixture can be adjusted to control the nucleation and growth process of the precipitate. If the pH value of the alkaline mixture is too high, the time required for the precipitation reaction is very short, the precipitation process is difficult to control, and large precipitate aggregates are likely to form. If the pH value of the alkaline mixture is too low, the aqueous solution containing M ions is difficult to form precipitates. If the pH value of the alkaline mixture is controlled within the appropriate range, it is advantageous for the preparation of carbon composite oxide particles with low powder resistivity and appropriate median particle size Dv50.

[0065] In some embodiments, the reaction time of the precipitation reaction is in the range of 4 to 15 h, optionally in the range of 6 to 12 h. In some embodiments, the reaction time of the precipitation reaction can be selected from any one of 4 h, 6 h, 8 h, 12 h, and 15 h.

[0066] The reaction time of the precipitation reaction can be adjusted to control the nucleation and growth process of the precipitate. If the reaction time is too short, the nucleation and growth of the precipitate will be incomplete, resulting in poor crystallinity of the material. If the reaction time is too long, the precipitate will continue to grow after nucleation, and the precipitate particles will be too large. If the reaction time of the precipitation reaction is controlled within the appropriate range, it is favorable for the preparation of carbon composite oxide particles with low powder resistivity and appropriate median particle size Dv50.

[0067] In some embodiments, the reaction temperature of the precipitation reaction is in the range of 30 to 80° C., optionally in the range of 40 to 60° C. In some embodiments, the reaction temperature of the precipitation reaction can be selected from any one of 40° C., 50° C., 60° C., and 80° C.

[0068] The reaction temperature of the precipitation reaction can be adjusted and controlled to control the nucleation and growth process of the precipitate. If the reaction temperature is too low, the nucleation and growth of the precipitate will be incomplete, resulting in poor crystallinity of the material. If the reaction temperature is too high, the precipitate will grow too fast after nucleation, resulting in the formation of large precipitates. If the reaction temperature of the precipitation reaction is controlled within a suitable range, it is advantageous to prepare a precursor of an electrode active material with low powder resistivity and a suitable median particle size Dv50. In addition, the preparation method disclosed in the present application has a low reaction temperature, which is different from the preparation method of a normal electrode active material or a normal precursor that needs to be reacted at a high temperature, and reduces energy consumption, reduces costs, and is advantageous for popularization and application.

[0069] In some embodiments, a weak alkaline solution is added to the mixed solution before adjusting and controlling the pH value of the mixed solution to be alkaline. The hydroxyl groups in the weak alkaline solution are slowly ionized from the solution, which controls the nucleation process of the precipitate, increases the nucleation rate of M ions on the carbon source, and avoids rapid growth and precipitation of the precipitate. The M ions adsorbed on the carbon source have enough time to disperse the nucleation, which increases the dispersibility of the carbon composite oxide particles and is convenient for adjusting and controlling the particle size of the carbon composite oxide, which is advantageous for preparing carbon composite oxide particles with low powder resistivity and appropriate median particle size Dv50.

[0070] In some embodiments, the weak alkaline solution is added to the mixed solution after stirring the mixed solution for a certain period of time. In some embodiments, the weak alkaline solution is added to the mixed solution after stirring the mixed solution for 0.5 h. Stirring the mixed solution for a certain period of time improves the dispersibility of M ions and the carbon source, assists the adsorption of M ions on the carbon source, and contributes to the preparation of a precursor of an electrode active material with a high degree of dispersion and a uniform particle size. In some embodiments, the weak alkaline solution and the mixed solution are added in parallel to the reaction vessel, and the flow rate of the weak alkaline solution is 0.1 to 0.7 times, preferably 0.2 to 0.6 times, more preferably 0.4 times, the flow rate of the mixed solution. Controlling the flow rate of the weak alkaline solution to control the nucleation rate is advantageous for the preparation of carbon composite oxide particles with a high degree of dispersion and a uniform particle size.

[0071] In some embodiments, the weak alkaline solution is selected from one or more of ammonia water, ammonium bicarbonate aqueous solution, ammonium carbonate aqueous solution, sodium carbonate aqueous solution, and sodium bicarbonate aqueous solution. In some embodiments, the concentration of the weak alkaline solution is preferably 2 to 8 mol / L. The above materials are simple and easily available, which is convenient for the popularization and application of this method and allows for cost reduction.

[0072] In some embodiments, the carbon source is selected from one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, graphene, graphite, carbon fibers, and carbon microspheres. It can be understood that any carbon material can be used as the carbon source, further expanding the scope of application of this method.

[0073] In some embodiments, the aqueous solution containing M ions is prepared by dissolving one or more of sulfates, nitrates, oxalates, and halides containing M elements in water. The simplicity and availability of raw materials further enhances the versatility of this method.

[0074] In some embodiments, the precursor is dried at 100-200°C for 6-20h to obtain a precursor of an electrode active material. If the drying temperature is too low or the drying time is too short, the removal of moisture in the precursor is likely to be incomplete, and if the drying temperature is too high or the drying time is too long, the growth of agglomerates of carbon-composite oxide particles is likely to occur. Controlling the drying temperature and time is advantageous for preparing carbon-composite oxide particles with low powder resistivity and appropriate median particle size Dv50.

[0075] The third embodiment of the present application provides an electrode active material prepared by using the precursor of the electrode active material according to any one of the above embodiments as a raw material. The electrode active material prepared by using the precursor of the electrode active material has an optimized powder resistivity and particle size, a uniform and complete carbon coating layer, and the electronic conductivity, charging capacity and stability of the electrode active material are high, so that the capacity of the battery can be further increased, and the electrode active material does not require post-treatment of the carbon coating, which reduces the production cost.

[0076] An embodiment according to a fourth aspect of the present application provides an electrode active material comprising carbon-coated metal oxide particles, the metal oxide particles satisfying the following formula (2): A c M d O e (2) In formula (2), the A element is selected from one or more alkali metal elements or alkaline earth metal elements, the M element is selected from one or more transition metal elements having a relative atomic mass less than 65, and c>0, d>0, and e>0.

[0077] The alkali metal elements are the six metallic elements in Group IA of the periodic table other than hydrogen (H), namely lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr).

[0078] The alkaline earth metals refer to the Group IIA elements in the periodic table, which includes six elements: beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra).

[0079] The transition metal elements refer to a series of metal elements in the d and ds regions of the periodic table, where the d region elements include the elements in groups IIIB to VIIB and VIII of the periodic table, and the ds region includes the elements in groups IB to IIB of the periodic table.

[0080] In the electrode active material provided by this embodiment, the atomic mass of the transition metal element is relatively small, and when the carbon-coated metal oxide particles contain the same number of A ions, they have a higher charge capacity per gram, the material remaining after discharge is lighter, and the weight of the total electrode pieces is smaller, which can improve the proportion of the electrode active material in the battery and the energy density.

[0081] In some embodiments, the A element is selected from one or more of Li, Na, K, Mg, and Ca. The above-mentioned metal oxides have high charge capacity per gram and high energy density, and the raw materials are abundant and easily available, suitable for various batteries, and have excellent application prospects.

[0082] In some embodiments, the metal oxide is Li 2 M 1 O 2 , Li 2 M 2 O 3 , Li 3 M 3 O 4 , Li 5 M 4 O 4 , Li 6 M 5 O 4 wherein M 1 is selected from one or more of Ni, Co, Fe, Mn, and Cu, and M 2 is selected from one or more of Mn, Sn, Mo, Ru, and Ir, and M3 is selected from one or more of V, Nb, Cr, and Mo; M 4 is selected from one or more of Fe, Cr, V, and Mo, and M 5 is selected from one or more of Co, V, Cr, and Mo.

[0083] In some embodiments, the shape, composition, structure, surface valence state and electrochemical performance of the electrode active material can be adjusted by controlling the type and ratio of the M element in the metal oxide. In some embodiments, the M element has abundant valence states, and the valence states of the M element in the metal oxide are all lower than its own highest oxidation valence state. The metal oxide has high charge capacity per gram, high energy density and good application prospects.

[0084] In some embodiments, the metal oxide is Li 2 NiO 2 , Li 2 CuO 2 , Li 2 MnO 3 , Li 3 VO 4 , Li 5 FeO 4 , Li 6 Chief of Staff 4 The preparation method of the above-mentioned lithium-rich metal oxide is mature, has high charge capacity per gram and high energy density, can meet the demand for rechargeable lithium batteries used in next-generation large-scale power grid storage and electric vehicles, and has high application prospects.

[0085] In some embodiments, the molar ratio of A element to M element is c:d≧2, calculated based on the total moles of the elements in the electrode active material. In the metal oxide, the more A atoms are relative to M atoms, the higher the charge capacity per gram of the electrode active material.

[0086] In some embodiments, the carbon content of the electrode active material is 2 wt% to 20 wt%, and optionally 5 wt% to 15 wt%, based on the total weight of the electrode active material. In some embodiments, the carbon content of the electrode active material is 2 wt% to 20 wt%, and optionally 5 wt% to 15 wt%, based on the total weight of the carbon-coated metal oxide. With an appropriate carbon coating content, the electrode active material has low powder resistivity, high material stability and electronic conductivity, and excellent carbon coating effect, which is advantageous for improving battery capacity.

[0087] In some embodiments, the electrode active material comprises a doping element, and the ratio of the solubility product constant of the hydroxide of the doping element to each of the hydroxides of the M element is 10 -5 ~10 5 and the doping element can be selected from one or more of Mg, Zn, Al, and Ti. The electrode active material can include a doping element to further improve the stability of the electrode active material. In some embodiments, the solubility product refers to the dissolution equilibrium constant of a precipitate, K sp The solubility product reflects the dissolving ability of a poorly soluble electrolyte. The ratio of the solubility product constants of the hydroxide of the doping element and the hydroxide of the M element is 10 -5 ~10 5 Therefore, the difference in solubility product between the hydroxide of the doping element and the hydroxide of the M element is too large, which can result in uneven doping and even the precipitation of the doping element alone. This maximizes the utility of the doping element and contributes to improving the charge capacity and energy density per gram of the electrode active material.

[0088] In some embodiments, the powder resistivity of the carbon coated metal oxide particles is less than 1000 Ω·cm, optionally less than 350 Ω·cm, more optionally less than 10 Ω·cm, and even more optionally less than 5 Ω·cm. In some embodiments, the powder resistivity of the carbon coated metal oxide particles is optionally less than 100 Ω·cm, and even more optionally less than 50 Ω·cm. In some embodiments, the powder resistivity of the carbon-coated metal oxide particles is optionally 1.24 Ω·cm, 2.12 Ω·cm, 2.83 Ω·cm, 3.18 Ω·cm, 6.54 Ω·cm, 10.13 Ω·cm, 17.24 Ω·cm, 21.34 Ω·cm, 25.36 Ω·cm, 32.41 Ω·cm, 35.76 Ω·cm, 45.32 Ω·cm, 48.35 Ω·cm, 50.13 Ω·cm, 56.21 Ω·cm, 60.28 Ω·cm, 81.22 Ω·cm, 89.13 Ω·cm, 236.11 Ω·cm, 313.87 Ω·cm. The carbon-coated metal oxide particles provided by this embodiment have low powder resistivity, high material stability and electronic conductivity, and good carbon coating effect, which is favorable for improving battery capacity.

[0089] In some embodiments, the median particle size Dv50 of the carbon-coated metal oxide particles is in the range of 100 to 900 nm, and optionally in the range of 300 to 700 nm. In some embodiments, the median particle size Dv50 of the carbon-coated metal oxide particles is in the range of 100 to 800 nm, and optionally in the range of 400 to 900 nm, and more optionally in the range of 200 to 600 nm. The carbon-coated metal oxide particles provided by the present application have an appropriate median size, a short ion transmission path during charging, high kinetics, and a higher charge capacity per gram, and at the same time, have an appropriate specific surface area, and are less likely to cause a decrease in charge capacity per gram due to aggregation.

[0090] In an embodiment according to the fifth aspect of the present application, there is provided a method for preparing an electrode active material, comprising providing carbon-composite oxide particles, the oxide satisfying the following formula (1): M a O b (1) In formula (1), M element is selected from one or more transition metal elements having a relative atomic mass of less than 65, a>0, b>0; The carbon-composite metal oxide particles and the A source are sintered to obtain carbon-coated metal oxide particles, and the metal oxide satisfies the following formula (2): A c M d O e (2) In formula (2), the A element is selected from one or more of alkali metal elements or alkaline earth metal elements, the M element is selected from one or more of transition metal elements having a relative atomic mass less than 65, and c>0, d>0, and e>0.

[0091] In some embodiments, the carbon composite oxide particles are composite materials containing carbon and oxide particles. It is understood that the carbon and oxide particles can be composited by any method, such as physical mixing, chemical composite, etc. Specifically, the carbon and oxide particles can be composited by stirring, grinding, ultrasonic, in-situ growth, grafting, etc.

[0092] In some embodiments, M a O b is M 1 O.M. 2 O 2 , M 3 2 O 5 , M 4 2 O 3 , M 5 O. 1 contains one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, and Cu, and M 2 contains one or more of Mn, Sn, Mo, Ru, and Ir, 3 contains one or more of V, Nb, Cr, and Mo, and M 4 contains one or more of Fe, Cr, V, and Mo, and M 5 contains one or more of Co, V, Cr, and Mo.

[0093] In some embodiments, the A source is any one or more alkali metal or alkaline earth metal containing raw material selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium acetate, sodium hydroxide, sodium carbonate, sodium oxide, sodium oxalate, sodium acetate.

[0094] In some embodiments, before sintering the carbon composite metal oxide particles and the source A, the carbon composite metal oxide particles and the source A are uniformly mixed to achieve uniform sintering. The carbon composite metal oxide particles and the source A can be uniformly mixed by any method, and the uniformity of the mixing can be improved by, for example, mechanical stirring, ball milling, chemical mixing, or the like.

[0095] In some embodiments, the sintering process is carried out in an atmosphere containing an inert gas to improve the purity of the sintered product. The atmosphere may be one or more of nitrogen, argon, and a hydrogen / argon mixture. The inert gas may be any inert gas, such as nitrogen, argon, etc.

[0096] In some embodiments, after the carbon composite metal oxide particles and the A source are sintered, the sintered product is crushed and / or sieved to obtain carbon-coated metal oxide particles.

[0097] The carbon-coated metal oxide particles prepared by the above method have high integrity of the outer carbon layer coating and low powder resistivity of the material. In addition, the surface carbon layer in the carbon composite oxide particles is effectively utilized to suppress the growth and aggregation of metal oxide particles during the sintering process, and the particle size of the metal oxide particles is limited to the submicron to nano order, so that the ion transmission path during the charging process of the carbon-coated metal oxide particles is short, the kinetics is high, and the charging capacity per gram is higher. At the same time, the post-treatment of the carbon coating on the carbon-coated metal oxide particles can be avoided, which effectively improves the stability of the carbon-coated metal oxide particles and reduces the manufacturing cost.

[0098] In some embodiments, the powder resistivity of the carbon composite oxide particles is less than 100 Ω·cm, and optionally less than 10 Ω·cm. The carbon composite oxide particles have low powder resistivity and the carbon element is highly uniform and well dispersed, so that the electrode active material prepared using the carbon composite oxide particles as a precursor does not require post-treatment of carbon coating, which solves the adverse effects of the normal post-treatment of carbon coating, improves the stability of the electrode active material, and reduces the manufacturing cost. At the same time, the carbon composite oxide particles have low powder resistivity and good carbon dispersion, so that the carbon-coated metal oxide particles prepared using the carbon composite oxide particles as a precursor have high coating integrity of the carbon layer, and the powder resistivity of the carbon-coated metal oxide particles is low, thereby improving the battery capacity.

[0099] In some embodiments, the median particle size Dv50 of the carbon composite oxide particles is in the range of 10 to 200 nm, and optionally in the range of 20 to 100 nm. Controlling the median particle size of the carbon composite oxide particles within an appropriate range is advantageous for controlling the particle size of the prepared carbon-coated metal oxide, reducing the powder resistivity of the carbon-coated metal oxide, and improving the charge capacity per gram.

[0100] In some embodiments, the carbon content in the carbon composite oxide particles is 10wt%-40wt%, and optionally 20wt%-30wt%, based on the total weight of the carbon composite oxide particles. Controlling the carbon content in the carbon composite oxide particles within an appropriate range is advantageous for reducing the powder resistivity of the carbon-coated metal oxide particles and improving their charge capacity per gram.

[0101] In some embodiments, the sintering temperature is in the range of 500-700° C., optionally in the range of 550-650° C., and / or the sintering time is in the range of 4-20 h, optionally in the range of 8-12 h. In some embodiments, the sintering temperature can be selected from 550° C., 590° C., 600° C., 610° C., 620° C., and 650° C. In some embodiments, the sintering time can be selected from 8 h, 10 h, and 12 h.

[0102] If the sintering temperature is too low or the sintering time is too short, the carbon-coated metal oxide particles will have poor crystallinity, incomplete phases, and low charge capacity per gram. If the sintering temperature is too high or the sintering time is too long, the median particle size Dv50 of the carbon-coated metal oxide particles will be too large, the delithiation pathway will be large, the kinetics will be poor, and the charge capacity per gram will be low. Controlling the sintering temperature and / or time within the appropriate range is favorable for preparing carbon-coated metal oxide particles with low powder resistivity, appropriate median particle size Dv50, and high charge capacity per gram.

[0103] In some embodiments, the A source is selected from one or more of an oxide, salt, or hydroxide of an alkali metal or alkaline earth metal, such as one or more of lithium oxide, sodium oxide, or magnesium oxide. This method is versatile and can synthesize multiple types of carbon-coated metal oxide particles as needed.

[0104] In some embodiments, the A source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, and lithium acetate, and the molar ratio of the lithium element in the A source to the M element in the carbon composited oxide particles is in the range of 5.5 to 1. In some embodiments, the molar ratio of the lithium element in the A source to the M element in the carbon composited oxide particles is in the range of 5.2 to 1. The lithium-excess metal oxide prepared by this method exhibits low powder resistivity and high charge capacity per gram.

[0105] In some embodiments, the carbon composite oxide particles are prepared by a liquid phase precipitation method, which involves a precipitation reaction in which the desired product is precipitated as a solid phase in a solution, and this method is simple, low-cost, and widely applicable.

[0106] An embodiment according to a sixth aspect of the present application provides a pole piece comprising a current collector and an electrode active material layer provided on at least one surface of the current collector and comprising an electrode active material according to any embodiment, the pole piece allowing the battery to have a high capacity.

[0107] A seventh embodiment of the present application provides a battery comprising the electrode active material or pole piece of any one of the embodiments, the battery having a high capacity. Working Example

[0108] The following describes the examples of the present application. The embodiments described below are illustrative and are intended to interpret the present application, and cannot be understood as limitations of the present application. In the examples, specific techniques or conditions are not specified, and are performed according to the techniques, conditions, or product specifications described in documents in this field. Reagents or instruments used without specifying the manufacturer are all ordinary products available on the market.

[0109] In the following examples, Fe 2 O 3 As an example, Fe(OH) 3 The precursor was obtained and dehydrated to give Fe 2 O 3 The precursor of the electrode active material to obtain @C is provided, and the specific preparation method is as follows: Example 1

[0110] The characteristics and performance of the present application will be described in more detail below with reference to examples.

[0111] FeSO 4 7H 2Using O as a raw material, distilled water is added to prepare a solution with an Fe element concentration of 5 mol / L. Carbon black is then added to the above solution under stirring conditions, and an appropriate amount of carbon black is added so that the mass content of carbon element in the product is 25% to obtain a mixed liquid.

[0112] Preparation of solution A: Prepare ammonium bicarbonate solution with a concentration of 5 mol / L. Preparation of solution B: Prepare sodium hydroxide solution with a concentration of 2 mol / L. The mixed liquid is put into the reaction vessel, solution A is put into the reaction vessel 0.5 h after the mixed liquid is added, and solution B is put into the reaction vessel 1 h after the mixed liquid is added, to obtain an alkaline mixed liquid, the flow rate of solution A is 0.4 times that of the mixed liquid, the flow rate of solution B is 0.1 times that of the mixed liquid, the pH value of the alkaline mixed liquid is 9, the alkaline mixed liquid is precipitated at a stirring intensity of 300 rpm, the reaction temperature of the precipitation reaction is 50°C, and the reaction time of the precipitation reaction is 8 hours.

[0113] After the reaction is completed, the precipitate is extracted by filtration or centrifuged, and then wet-washed several times with distilled water or absolute ethanol to obtain the precursor.

[0114] The precursor was placed in an oven and dried at 150℃ for 12 hours to obtain carbon-composite iron trioxide particles. 2 O 3 It is written as @C. Example 2

[0115] In this embodiment, a precursor of an electrode active material is prepared in a manner similar to that of Example 1, except that the pH value of the alkaline mixed solution in Example 1 is set to 10, and other operation flows are maintained as they are. Example 3

[0116] In this embodiment, a precursor of an electrode active material is prepared in a manner similar to that of Example 1, except that the pH value of the alkaline mixed solution in Example 1 is set to 11, and other operation flows are maintained as they are. Example 4

[0117] In this embodiment, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the pH value of the alkaline mixed solution in Example 3 is set to 12, and other operation flows are maintained as they are. Example 5

[0118] In this embodiment, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the pH value of the alkaline mixed solution in Example 3 is set to 13, and other operation flows are maintained as they are. Example 6

[0119] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction time of the precipitation reaction in Example 3 is set to 4 hours, and other operation flows are maintained as they are. Example 7

[0120] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction time of the precipitation reaction in Example 3 is set to 6 hours, and other operation flows are maintained as they are. Example 8

[0121] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction time of the precipitation reaction in Example 3 is set to 12 hours, and other operation flows are maintained as they are. Example 9

[0122] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction time of the precipitation reaction in Example 3 is set to 15 hours, and other operation flows are maintained as they are. Example 10

[0123] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction temperature of the precipitation reaction in Example 3 is set to 30°C, and other operation flows are maintained as they are. Example 11

[0124] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction temperature of the precipitation reaction in Example 3 is set to 40°C, and other operation flows are maintained as they are. Example 12

[0125] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction temperature of the precipitation reaction in Example 3 is set to 60°C, and other operation flows are maintained as they are. Example 13

[0126] In this example, a precursor of an electrode active material is prepared in a manner similar to that of Example 3, except that the reaction temperature of the precipitation reaction in Example 3 is set to 80°C, and other operation flows are maintained as they are. Example 14

[0127] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the amount of carbon black added in Example 3 is reduced so that the mass content of carbon element in the product is 10%. Example 15

[0128] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the amount of carbon black added in Example 3 is reduced so that the mass content of carbon element in the product is 20%, and other operation flows are maintained as they are. Example 16

[0129] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the amount of carbon black added in Example 3 is increased so that the mass content of carbon element in the product is 30%, and other operation flows are maintained as they are. Example 17

[0130] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the amount of carbon black added in Example 3 is increased so that the mass content of carbon element in the product is 40%, and other operation flows are maintained as they are. Example 18

[0131] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the carbon source in Example 3 is replaced with carbon nanotubes (CNTs) instead of carbon black, the mass of the added carbon nanotubes is set so that the mass content of carbon element in the product is 20%, and other operation flows are maintained as they are. Example 19

[0132] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the carbon source in Example 3 is replaced with graphite (Gr) instead of carbon black, the mass of graphite added is such that the mass content of carbon element in the product is 18%, and other operation flows are maintained as they are. Example 20

[0133] This example shows the metal salt FeSO in Example 3. 4 7H 2 NiSO 4 6H 2 O; the pH value of the alkaline mixed solution was set to 11.8; the reaction time of the precipitation reaction was set to 8 h; the reaction temperature was set to 55° C.; the mass of carbon black added was such that the mass content of carbon element in the product was 23%; and other operation flows were maintained as they were, so as to provide a precursor of an electrode active material prepared in a manner similar to that of Example 3. Example 21

[0134] This example shows the metal salt FeSO in Example 3. 4 7H 2 CuSO 4 5H 2The electrode active material precursor was prepared in a manner similar to that of Example 3, except that the alkaline mixed solution was replaced with O, the pH value of the alkaline mixed solution was set to 11.6, the reaction time of the precipitation reaction was set to 6 h, the reaction temperature was set to 45° C., the mass of carbon black added was such that the mass content of carbon element in the product was 22%, and other operation flows were maintained as they were. Example 22

[0135] This example shows the metal salt FeSO in Example 3. 4 7H 2 CoSO 4 7H 2 The electrode active material precursor was prepared in a manner similar to that of Example 3, except that the alkaline mixed solution was replaced with O, the pH value of the alkaline mixed solution was set to 12, the reaction time of the precipitation reaction was set to 10 h, the reaction temperature was set to 60° C., the mass of carbon black added was such that the mass content of carbon element in the product was 24%, and other operation flows were maintained as they were. Comparative Example 1

[0136] This example provides a precursor of an electrode active material prepared in a manner similar to that of Example 3, except that the pH value of the alkaline mixed solution in Example 3 is set to 8, the mass of carbon black added is such that the mass content of carbon element in the product is 45%, and other operation flows are maintained as they are. Comparative Example 2

[0137] This comparative example provides a precursor of an electrode active material prepared in a manner similar to that of Comparative Example 1, except that the pH value of the alkaline mixed solution in Comparative Example 1 is set to 14, the reaction time of the precipitation reaction is set to 2 h, the mass content of carbon element in the product is 5%, and other operation flows are maintained as they are. Comparative Example 3

[0138] This comparative example provides a precursor of an electrode active material prepared in a manner similar to that of Comparative Example 1, except that the pH value of the alkaline mixed solution in Comparative Example 1 is set to 11, the reaction time of the precipitation reaction is set to 2 h, the reaction temperature of the precipitation reaction is set to 90° C., the mass content of carbon element in the product is 16%, and other operation flows are maintained as they are. Comparative Example 4

[0139] This comparative example provides a precursor of an electrode active material prepared in a manner similar to that of Comparative Example 1, except that the pH value of the alkaline mixed solution in Comparative Example 1 is set to 11, the reaction time of the precipitation reaction is set to 20 h, the reaction temperature of the precipitation reaction is set to 25° C., the mass content of carbon element in the product is 35%, and other operation flows are maintained as they are. Comparative Example 5

[0140] This comparative example provides a precursor of an electrode active material prepared in a manner similar to that of Comparative Example 1, except that no carbon black was added, the pH value of the alkaline mixed solution in Comparative Example 1 was set to 11, the reaction time of the precipitation reaction was set to 8 hours, the reaction temperature of the precipitation reaction was changed to 50°C, and the other operation flows were maintained as they were. Comparative Example 6

[0141] This comparative example is the same as that of Comparative Example 5. 2 O 3 and carbon black were mixed in a ball mill at a carbon mass ratio of 25% to prepare Comparative Example 6. The ball mill rotation speed was 200 rpm, and the ball mill was run for 6 hours. The product obtained by the preparation was treated with Fe 2 O 3 A precursor of an electrode active material was prepared in a manner similar to that of Comparative Example 1, except for the point indicated as / C.

[0142] The parameters relating to the carbon composite oxide particles of Examples 1 to 22 and Comparative Examples 1 to 6 are shown in Table 1 below. [Table 1] JPEG0007669527000002.jpg168140

[0143] In the following Examples and Comparative Examples, unless otherwise specified, the materials prepared by the methods described in the above Examples were selected as precursors of electrode active materials. Example 23

[0144] The characteristics and performance of the present application will be described in more detail below with reference to examples.

[0145] This embodiment provides an electrode active material, Li 5 FeO 4 Taking @C as an example, the specific preparation method is as follows:

[0146] Raw material mixture: Fe with 25% carbon content as the precursor of the electrode active material 2 O 3 Select @C and Fe 2 O 3 The Dv50 of @C is 10 nm, the powder resistivity is 1.02 Ω cm, and the A source is lithium hydroxide (LiOH H 2 O) was selected and added to a mechanical fusion machine in a metal molar ratio of Li:Fe of 5.1:1, and mixed by mechanical fusion method, with the rotation speed set to 300 rpm and the mixing time set to 6 h.

[0147] Sintering: The mixed raw materials are heated under nitrogen gas at a rate of 3°C / min up to a sintering temperature of 600°C, and after sintering for 10 hours, the temperature is naturally lowered to obtain the product.

[0148] Crushing and classification: The product is crushed, classified and sieved to obtain carbon-coated metal oxide particles (Li 5 FeO 4 @C) is obtained. Example 24

[0149] This example is the same as in Example 23, except that Fe 2 O 3 An electrode active material was prepared in a manner similar to that of Example 23, except that the Dv50 of @C was changed to 20 nm and the powder resistivity was changed to 0.56 Ω·cm. Example 25

[0150] This example is the same as in Example 23, except that Fe 2 O 3 An electrode active material was prepared in a manner similar to that of Example 23, except that the Dv50 of @C was changed to 60 nm and the powder resistivity was changed to 0.22 Ω·cm. Example 26

[0151] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared in a manner similar to that of Example 25, except that the Dv50 of @C was changed to 100 nm and the powder resistivity was changed to 3.58 Ω·cm. Example 27

[0152] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared in a manner similar to that of Example 25, except that the Dv50 of @C was changed to 200 nm and the powder resistivity was changed to 8.32 Ω·cm. Example 28

[0153] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared in a manner similar to that of Example 25, except that the carbon content of @C was changed to 10% and the powder resistivity was set to 15.34 Ω·cm. Example 29

[0154] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared in a manner similar to that of Example 25, except that the carbon content of @C was changed to 20% and the powder resistivity was set to 10.13 Ω·cm. Example 30

[0155] This example is the same as in Example 25. 2 O 3An electrode active material was prepared in a manner similar to that of Example 25, except that the carbon content of @C was changed to 30% and the powder resistivity was set to 0.48 Ω·cm. Example 31

[0156] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared in a manner similar to that of Example 25, except that the carbon content of @C was changed to 40% and the powder resistivity was set to 0.71 Ω·cm. Example 32

[0157] This example provides an electrode active material prepared in a manner similar to that of Example 25, except that the sintering temperature in Example 25 was changed to 500°C. Example 33

[0158] This example provides an electrode active material prepared in a manner similar to that of Example 25, except that the sintering temperature in Example 25 was changed to 550°C. Example 34

[0159] This example provides an electrode active material prepared in a manner similar to that of Example 25, except that the sintering temperature in Example 25 was changed to 650°C. Example 35

[0160] This example provides an electrode active material prepared in a manner similar to that of Example 25, except that the sintering temperature in Example 25 was changed to 700°C. Example 36

[0161] In this example, an electrode active material is prepared in a manner similar to that of Example 25, except that the sintering time in Example 25 was changed to 4 hours. Example 37

[0162] In this example, an electrode active material is prepared in a manner similar to that of Example 25, except that the sintering time in Example 25 was changed to 8 hours. Example 38

[0163] In this example, an electrode active material is prepared in a manner similar to that of Example 25, except that the sintering time in Example 25 was changed to 12 hours. Example 39

[0164] In this example, an electrode active material is prepared in a manner similar to that of Example 25, except that the sintering time in Example 25 was changed to 20 hours. Example 40

[0165] In this example, the carbon source in Example 25 was replaced with carbon nanotubes instead of carbon black, and the precursor Fe 2 O 3 @An electrode active material was prepared by a method similar to that of Example 25, except that the powder resistivity of the CNTs was 0.24 Ω·cm. Example 41

[0166] In this example, the carbon source in Example 25 was replaced with graphite instead of carbon black, and the precursor Fe 2 O 3 An electrode active material was prepared by substantially the same method as in Example 25, except that the powder resistivity of @Gr was 0.23 Ω·cm. Example 42

[0167] This example is the same as in Example 25. 2 O 3 An electrode active material was prepared by a method similar to that of Example 25, except that @C was changed to NiO@C, the Dv50 of NiO@C was changed to 58 nm, the powder resistivity was changed to 0.21 Ω·cm, the carbon content of NiO@C was changed to 23%, and the sintering temperature was changed to 620°C. Example 43

[0168] This example is the same as in Example 25. 2 O 3An electrode active material was prepared by a method similar to that of Example 25, except that @C was changed to CuO@C, the Dv50 of CuO@C was changed to 62 nm, the powder resistivity was changed to 0.25 Ω·cm, the carbon content of CuO@C was changed to 22%, and the sintering temperature was changed to 590°C. Example 44

[0169] This example is the same as in Example 25. 2 O 3 @C to Co 3 O 4 Change it to @C and then Co 3 O 4 The Dv50 of @C is 61 nm, the powder resistivity is 0.19 Ω cm, and the Co 3 O 4 An electrode active material was prepared by substantially the same method as in Example 25, except that the carbon content of @C was changed to 24% and the sintering temperature was changed to 610°C. Comparative Example 7

[0170] In this comparative example, the electrode active material is provided, and Li 5 FeO 4 Taking @C as an example, the specific preparation method is as follows:

[0171] Raw material mixture: Fe with 1% carbon content as the precursor of the electrode active material 2 O 3 Select @C and Fe 2 O 3 The Dv50 of @C is 320 nm, the powder resistivity is 25.16 Ω cm, and the A source is lithium hydroxide (LiOH H 2 O) was selected and added to a mechanical fusion machine in a metal molar ratio of Li:Fe of 5.1:1, and mixed by mechanical fusion method, with the rotation speed set to 300 rpm and the mixing time set to 6 h.

[0172] Sintering: The mixed raw materials are heated under nitrogen gas at a rate of 3°C / min up to a sintering temperature of 600°C, and after sintering for 10 hours, the temperature is naturally lowered to obtain the product.

[0173] Crushing and classification: The product is crushed, classified and sieved to obtain carbon-coated metal oxide particles (Li5 FeO 4 @C) is obtained. Comparative Example 8

[0174] This comparative example is the same as that of Comparative Example 7. 2 O 3 The Dv50 of @C was changed to 420 nm, the powder resistivity was changed to 36.78 Ω cm, and the Fe 2 O 3 @ Provide an electrode active material prepared in a manner similar to that of Comparative Example 7, except that the carbon content of C was 5%, the sintering temperature was changed to 750°C, and the other operation flow was maintained as it was. Comparative Example 9

[0175] This comparative example is the same as that of Comparative Example 7. 2 O 3 The Dv50 of @C was changed to 250 nm, the powder resistivity was set to 18.36 Ω cm, and the Fe 2 O 3 An electrode active material is prepared in a manner similar to that of Comparative Example 7, except that the carbon content of @C is 25%, the sintering temperature is changed to 450°C, the sintering time is changed to 2h, and the other operation flows are maintained as they are. Comparative Example 10

[0176] This comparative example is the same as that of Comparative Example 7. 2 O 3 The Dv50 of @C was changed to 350 nm, the powder resistivity was changed to 28.74 Ω cm, and the Fe 2 O 3 An electrode active material is provided that is prepared in a manner similar to that of Comparative Example 7, except that the carbon content of @C is 50%, the sintering temperature is changed to 800°C, the sintering time is changed to 22h, and the other operation flows are maintained as they are. Comparative Example 11

[0177] This comparative example is the same as the step of Comparative Example 5. 2 O 3 Prepare Fe 2 O 3 The Dv50 of Fe is 2500 nm, the powder resistivity is 68201.39 Ω cm, 2 O 3was used as the precursor of the electrode active material, and the other operation flow was the same as in Comparative Example 7. 5 FeO 4 An electrode active material was prepared in a manner similar to that of Comparative Example 7, except that the above-mentioned was used as the electrode active material. Comparative Example 12

[0178] This comparative example is the same as Comparative Example 6. 2 O 3 The mass of carbon black was adjusted to Fe 2 O 3 25% of the mass, Fe 2 O 3 The Dv50 of / C was set to 2600 nm and the powder resistivity was set to 2310.23 Ω·cm. This was used as a precursor of the electrode active material, and Li was 5 FeO 4 An electrode active material was prepared in a manner similar to that of Comparative Example 7, except that the other operation flows were maintained as they were.

[0179] The parameters relating to the carbon-coated metal oxide particles of Examples 23 to 44 and Comparative Examples 7 to 12 are shown in Table 2 below. [Table 2] Test Method

[0180] Median particle size Dv50: Refer to GB / T19077-2016 particle size distribution laser diffraction method, measured using a laser particle size analyzer Malvern Mastersizer 2000E, UK.

[0181] Measurement of carbon content: Using the carbon content analyzer Ccontentanalyzer, equipment model HCS-140, based on the measurement of the total carbon-sulfur content of steel, measure the carbon content in the powder by infrared absorption method (general method) GBT20123-2006 after high-frequency induction furnace combustion.

[0182] Measurement of powder resistivity: Dry the powder of carbon composite oxide particles or carbon-coated metal oxide particles, weigh an appropriate amount of powder, and then use a powder resistivity tester, model ST2722 digital four-probe, to measure the powder resistivity of the sample in accordance with GB / T30835-2014, Carbon composite lithium iron phosphate positive electrode material for lithium ion batteries.

[0183] Initial charge capacity per gram test of carbon-coated metal oxide particles: Carbon-coated metal oxide particles, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methylpyrrolidone (NMP) in a mass ratio of 80:10:10, and thoroughly stirred to mix uniformly to obtain a positive electrode slurry. The positive electrode slurry is applied to one surface of a positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode piece is obtained. Ethylene carbonate (EC) and methyl ethyl carbonate (EMC) are uniformly mixed in a mass ratio of 30:70 to obtain an organic solvent, and further lithium salt LiPF 6 The above-mentioned organic solvent was dissolved and mixed uniformly to obtain an electrolyte solution, in which LiPF 6 The concentration of is 1 mol / L. A lithium sheet is used as an electrode pair, and assembled with a positive electrode piece to form a button battery. The button battery is charged at a constant current of 0.1C up to 4.25V, left to stand for 5 minutes, and the charge capacity of the button battery at this time is recorded. The initial charge capacity per gram is determined by dividing the charge capacity of the battery by the mass of the carbon-coated metal oxide particles. Test results

[0184] The prepared carbon composite oxide particles were characterized by shape using a scanning electron microscope (SEM). As a result, as shown in FIG. 1, there are many particles with uniform morphology, firm structure, and uniform distribution. The carbon composite oxide particles were further characterized by shape using a transmission electron microscope (TEM). As shown in FIG. 2, as can be seen from the light and dark contrast in the figure, the oxide particles are uniformly coated in the carbon, the particle size of the oxide particles is uniform, and no obvious aggregation occurs. The carbon composite oxide particles prepared in Example 3 were subjected to a structure test combined with X-ray diffraction (XRD). As can be seen from the crystal type comparison in FIG. 3, the synthesis product contains Fe 2 O 3 @C.

[0185] The test results of the powder resistivity and median particle size of the carbon composite oxide particles of Examples 1 to 22 and Comparative Examples 1 to 6 are shown in Table 3 below. [Table 3]

[0186] As can be seen from a comparison of Examples 1 to 22 and Comparative Examples 1 to 4 with Comparative Examples 5 and 6, the carbon composite oxide particles disclosed in the present application have low resistivity, appropriate median particle size and carbon content.

[0187] As can be seen from the comparison of Examples 1-5 and Comparative Examples 1 and 2, the powder resistivity and median particle size of the carbon composite oxide particles can be adjusted by controlling the pH value of the alkaline mixture. The appropriate pH value of the alkaline mixture is advantageous for preparing carbon composite oxide particles with low powder resistivity and appropriate median particle size. As can be seen from Examples 6-13, the powder resistivity and median particle size of the carbon composite oxide particles can be adjusted by controlling the reaction temperature or reaction time of the precipitation reaction. The appropriate reaction temperature and reaction time of the precipitation reaction are advantageous for preparing carbon composite oxide particles with low powder resistivity and appropriate median particle size. As can be seen from the comparison of Examples 14-17 and Comparative Examples 3 and 4, the powder resistivity and median particle size of the carbon composite oxide particles can be adjusted by controlling the carbon content of the carbon composite oxide particles. The median particle size Dv50 and powder resistivity of the carbon composite oxide particles first decrease and then increase as the carbon content increases.

[0188] As can be seen from Examples 18-19, the method for preparing carbon composite oxide particles disclosed in the present application is suitable for various carbon sources such as carbon nanotubes and graphite.

[0189] As can be seen from Examples 20 to 22, the method for preparing carbon composite oxide particles disclosed in the present application is suitable for preparing various carbon composite oxides such as carbon composite copper oxide and nickel carbon composite oxide, and the prepared products all have low powder resistivity and appropriate median particle size.

[0190] The shape of the carbon-coated metal oxide particles was characterized using a transmission electron microscope (TEM). As shown in FIG. 4, the light-dark contrast in the figure shows that the active material particles are uniformly coated in the carbon, the particle size is in the nano-order, and no obvious aggregation occurs. The carbon-coated metal oxide particles prepared by the method of Example 25 were tested by combining with X-ray diffraction (XRD). As shown in FIG. 5, the crystal structure can be compared to show that the synthesis product is a carbon-coated lithium-excess iron oxide, and Li 5 FeO4 The initial charging curve of the battery assembled using this as an electrode material is indicated as @C and is shown in FIG. 6, from which the initial charging capacity per gram of the battery is calculated.

[0191] The test results of the carbon-coated metal oxide particles of Examples 23 to 44 and Comparative Examples 7 to 12 are shown in Table 4 below. [Table 4]

[0192] As can be seen from a comparison of Examples 23-44 and Comparative Examples 7-12, the carbon-coated metal oxide particles prepared by sintering the above-synthesized carbon composite oxide particles, which have a uniform particle size distribution, low powder resistivity, and good dispersibility, under certain conditions, have low powder resistivity, appropriate median particle size Dv50, and high charge capacity per gram.

[0193] As can be seen from the comparison of Examples 23-27 and Comparative Examples 7-9, the powder resistivity and median particle size of the carbon-coated metal oxide particles can be adjusted by adjusting and controlling the median particle size Dv50 of the carbon-composite oxide particles. The appropriate median particle size Dv50 of the carbon-composite oxide particles is advantageous for preparing carbon-coated metal oxide particles with low powder resistivity, appropriate median particle size, and high charge capacity per gram. As can be seen from Examples 28-31, the powder resistivity and median particle size of the carbon-coated metal oxide particles can be adjusted by adjusting and controlling the carbon content of the carbon-composite oxide particles. The appropriate carbon content in the carbon-composite oxide particles is advantageous for preparing carbon-coated metal oxide particles with low powder resistivity and appropriate median particle size, which in turn improves the battery capacity per gram. As can be seen from the comparison of Examples 32-39 and Comparative Examples 9-10, the powder resistivity and median particle size of the carbon-coated metal oxide particles can be adjusted by adjusting and controlling the sintering temperature and time.

[0194] As can be seen from Examples 40 to 41, any of the carbon composite oxides prepared from various carbon sources can be used to prepare carbon-coated metal oxide particles with low powder resistivity and high charge capacity per gram.

[0195] As can be seen from Examples 42-44, the method for preparing carbon-coated metal oxide particles disclosed herein can effectively reduce the amount of Li 2 NiO 2 @C, Li 2 CuO 2 @C, Li 6 Chief of Staff 4 The method is suitable for preparing various electrode active materials such as @C, and the prepared products all have low powder resistivity, appropriate median particle size, and high charge capacity per gram, demonstrating the versatility of this preparation method.

[0196] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment that has substantially the same configuration as the technical idea and exhibits similar effects within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of are added to the embodiment, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the gist of the present application.

Claims

1. A method for preparing an electrode active material, comprising the steps of: The method comprises: The present invention provides carbon-composite oxide particles, in which the oxide satisfies the following formula (1): M a O b (1) In formula (1), M element is selected from one or more of Fe, Ni, Cu, and Co, and a>0 and b>0 are satisfied; sintering the carbon composite oxide particles and a Li source to obtain carbon-coated metal oxide particles, in which the metal oxide is selected from one or more of Li2NiO2, Li2CuO2, Li5FeO4, and Li6CoO4; The method for preparing an electrode active material, wherein the carbon-composite oxide particles have a median particle size Dv50 in the range of 10 to 200 nm.

2. 2. The method for preparing an electrode active material according to claim 1, wherein the powder resistivity of the carbon-composite oxide particles is less than 100 Ω·cm.

3. The method for preparing an electrode active material as described in claim 2, characterized in that the powder resistivity of the carbon-composite oxide particles is less than 10 Ω·cm.

4. 3. The method for preparing an electrode active material according to claim 1, wherein the median particle diameter Dv50 of the carbon-composite oxide particles is within a range of 20 to 100 nm.

5. 3. The method for preparing an electrode active material according to claim 1, wherein the carbon content in the carbon-composite oxide particles is 10 wt % to 40 wt % based on the total weight of the carbon-composite oxide particles.

6. A method for preparing an electrode active material as described in claim 5, characterized in that the carbon content in the carbon-composite oxide particles is 20 wt % to 30 wt % based on the total weight of the carbon-composite oxide particles.

7. the temperature of the sintering process is in the range of 500 to 700°C; and / or 3. The method for preparing an electrode active material according to claim 1, wherein the sintering time is within a range of 4 to 20 hours.

8. The temperature of the sintering process is in the range of 550 to 650°C, and / or The method for preparing an electrode active material according to claim 7, wherein the sintering time is within the range of 8 to 12 hours.

9. 3. The method for preparing an electrode active material according to claim 1, wherein the Li source is selected from one or more of an oxide, a salt, and a hydroxide of Li.

10. The method for preparing an electrode active material according to claim 1 or 2, characterized in that the Li source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, and lithium acetate, and the molar ratio of the lithium element in the Li source to the M element in the carbon-composite oxide particles is within a range of 1 to 5.

5.

11. 3. The method for preparing an electrode active material according to claim 1, wherein the carbon-composite oxide particles are prepared by a liquid phase precipitation method.

Citation Information

Patent Citations

  • Preparation method and application of fluorine phosphorus lithium vanadate

    CN112864359A